PENGARUH KONSENTRASI DAN LAMA PERENDAMAN BAHAN PENGAWET DAUN TEMBELEKAN (Lantana camara L.) PADA KAYU BAYUR (Pterospermum sp.) TERHADAP SERANGAN RAYAP TANAH (Coptotermes sp.) - Salmayanti, Salmayanti; Ariyanti, Ariyanti; Hapid, Abdul (Jurnal Warta Rimba, 2013)
There are about Â± 4.000 wood species in Indonesia. In small amount of that woods were categorized as durable wood (Class I and II) while mostly (80-85%) were categorized non-durable wood (Class III to V). This study was aimed to determine the effects of Lantana camara L. leaves extracts as preservation material of Pterospermum sp wood on the Coptotermes sp. attacks. The experiment was conducted in the laboratory of Forestry science, Forestry Faculty, Tadulako University, from May to June 2013. The study was using completely randomized design with pattern. The treatment of study was applying two factors. First, concentration of L.camara L. extracts with three levels, namely ;9,09 g (K1), 13,04 g (K2), and 16,66 g (K3). Second, Dipping time with three levels, namely: 1 day (L1), 3 days (L3), and 5 days (L5). Data was analyzed by using analysis (Anova).The results showed that water contents and density of Pterospermum sp. woods was 8,37% and 0,321 g/cmÂ³, respectively. Hence, the highest weight loss was achieved by K1L1 combination treatment (9,99%) while the lowest was achieved by K3L5 combination treatment (8,93%). Generally, concentration of L.camara L. and dipping time extracts did not affect significantly the weight loss of Pterospermum sp woods. Keywords: Concentration, Dipping, Lantana camara L., Pterospermum sp., Coptotermes sp.